Introduction to Embedded Systems - Jiménez, Manuel; Palomera, Rogelio; Couvertier, Isidoro (Springer, 2014)
The first years of the decade of 1970 witnessed the development of the first microprocessor designs in the history of computing. Two remarkable events were the development of the 4004, the first commercial, single-chip microprocessor created by Intel Corporation and the TMS1000, the first single-chip microcontroller by Texas Instruments. Based on 4-bit architectures, these early designs opened a whole new era in terms of technological advances. Several companies such as Zilog, Motorola, Rockwell, and others soon realized the potential of microprocessors and joined the market with their own designs. Today, we can find microprocessors from dozens of manufacturers in almost any imaginable device in our daily lives: from simple and inexpensive toys to sophisticated space ships, passing through communication devices, life supporting and medical equipment, defense applications, and home appliances. Being such a ubiquitous device, it is not surprising that more and more people today need to understand the basics of how microprocessors work in order to harness and exploit their capacity. Among these people we find enthusiastic hobbyists, engineers without previous experience, electronic technology students, and engineering students. Throughout the years, we have encountered many good books on microprocessors and embedded systems. However, most of these books share the same basic type of problems: they were written either for one specific microprocessor and their usefulness was limited in scope to the device they presented, or were developed without a specific target processor in mind lacking the practical side of teaching embedded systems. Aware of these realities, we have developed an introductory-level book that falls in the middle of these two extremes. This book has been written to introduce the reader to the subjects of microprocessors and embedded systems, covering architectural issues, programming fundamentals, and the basics of interfacing. As part of the architectural aspects, it covers topics in processor organization, emphasizing the typical structure of today’s microcontrollers, processor models, and programming styles. It also covers fundamentals on computer data representations and operations, as a prelude to subjects in embedded software development. The presented material is rounded off with discussions that cover from the basics of input/output systems to using all sorts of embedded peripherals and interfacing external loads for diverse applications. Most practical examples use Texas Instruments MSP430 devices, an intuitive and affordable platform. But the book is not limited to the scope of this microcontroller. Each chapter has been filled with concepts and practices that set a solid design foundation in embedded systems which is independent from the specific device being used. This material is then followed by a discussion of how these concepts apply to particular MSP430 devices. This allows our readers to first build a solid foundation in the underlying functional and design concepts and then to put them in practice with a simple and yet powerful family of devices.
Using Microcontrollers and the MSP430
Keywords: Embedded computer systems; Systems engineering